THE INFLUENCE OF DIGITAL MEDIA FRAMING ON THE CONSTRUCTION OF GENERATION Z'S PERCEPTION OF THE IRAN-USA CONFLICT - Romi Syahril; Priatna; A.Rafiq; Azhar Hutomo (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to understand and explore the influence of digital media framing on Generation Z's perceptions of the international conflict between Iran and the United States. Information circulating in digital media is never entirely neutral but is always shaped by geopolitical and ideological interests through a complex framing process. This research was implemented using a qualitative approach, relying on in-depth interviews with five Generation Z informants, selected using a purposive sampling technique. Thematic analysis of the interview data showed that digital media framing significantly influenced the formation of informants' perceptions. Western media tended to frame Iran as an aggressive entity, while alternative media and independent creators emphasized the United States as a provocative imperialist power. Generation Z's perceptions are formed through three main cognitive stages: sensation, attention, and interpretation. Digital literacy levels were identified as a crucial determinant. Highly literate informants were shown to be able to cross-verify news sources, while those with passive literacy tended to accept framing from a single platform. This study recommends strengthening digital literacy so that Generation Z becomes accustomed to verifying and forming objective opinions amidst the digital information maelstrom.